Dynamics of Dust Particles near Sun, Vega and Fomalhaut - Stamm, Johann Immanuel; Baumann, Carsten; Czechowski, Andrzej; Mann, Ingrid; Myrvang, Margaretha (UiT The Arctic University of Norway, 2018)
Poster presentation